EARNINGS AND THEIR MEASUREMENT - دمیان, فوزی (Dirasat in Economics and Business, 1977)
There are two distinct views to measure earnings of an organisation : (l) the revenue and expense view, and. (2) the asset and liability view. According to the revenue/expense view, earnings are defined in terms of the difference between revenues and expenses. The notion of proper "matching" of expenses with revenues is central to this view. Revenues represent accomplishments of an organization in producing and distributing goods or rendering services during a period. Expenses represent the resources used during the period to obtain current revenues. Earnings (revenue-expenses) are primarily an indicator of enterprise performance. Revenue/ expense view reflects the opinion of those who consider assets and liabilities to be primarily debits and credits that are left after appropriately matching costs with revenues to measure earnings for the period and are included to make the balance sheet.